Differences in the effects of aluminum/ytterbium/cobalt on the structural stability and electrochemical properties of nickel hydroxide. (February 2017) - Zhao, Tengqi; Zhu, Yanjuan; Li, Wenhua; Jian, Xiuwen
Graphical abstract: Highlights: Synergistic effect for Al/Yb/Co is better than binary doping. The Al-Yb-Co doped α-Ni(OH)2 exhibits excellent structural stability. Electrochemical properties of the ternary are better than the binary. Abstract: Alpha nickel hydroxide has better performance than commercial beta nickel hydroxide. However, the main defect is that α-phase is easily transformed to β-phase Ni(OH)2 upon aging in a strong alkaline solution. The different effects of the doping cations Al 3+, Yb 3+ and Co 2+ on the chemical composition, morphology, structure and electrochemical properties of Ni(OH)2 are studied, with the same doping ratio. The results demonstrate that the synergistic effect of the ternary doping samples is better than the binary. The Al-Yb-Co-Ni(OH)2 exhibits excellent structural stability, which can stay the pure α-phase in strong alkaline solutions over 60 days. The CV measurements demonstrate that the relevant electrode has the highest proton diffusion coefficient, indicating a higher electrochemical activity and faster reaction kinetics due to the fast ionic transportation. Moreover, the above electrode has the higher charge efficiency, better reversibility and cycle stability.